When Lying Becomes An Ordinary Thing: Ethics in The Post-Truth Era - Rianto, Puji (UI Scholars Hub, 2020)
In Indonesia, the post-truth phenomenon is usually seen more often as a literacy or legal problem. In fact, when understood as new forms of political dishonesty, post-truth must be seen as an ethical problem. This study examines the post-truth phenomenon that takes place in the political reality in Indonesia using communication ethic. The study uses two methods, rhetorical analysis to analysis of Hoax spread on social media and participatory observations in WhatsApp groups. This study found that post-truth basically occurs because of the low ethics of media users in producing, consuming, and sharing social media content. They intentionally created “dishonest facts” in order to achieve their own goals. People involved in post-truth are very ideological and lack social sensitivity. They only care about the narratives they want to build and receive. So, the truth becomes less important. This research suggests that political communication in the post-truth era must be based on the ethics of communication in order to build a strong and stable democracy, and people who use social media must consider the ethics of communication